2014
DOI: 10.1039/c3bm60312a
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone coating on cotton cloth – an approach to reduce attachment of live microbes

Abstract: Cloths coated with 4-sulfonylmethyl chalcone prevented the growth of Gram positive and Gram negative microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…coli was obviously displayed in all of the antibacterial fabrics (F8, F9, F10, F11, and F3) as compared to that in the pristine fabric, with an especially great reduction for antibacterial fabrics (F9, F10, F11, and F3) due to the fluorine component. Sivakumar et al previously reported that hydrophilic surfaces prevent bacterial attachment and hydrophobic organisms have a greater propensity to attach to hydrophobic surfaces than hydrophilic ones in their work. However, a few researchers have found that in in vitro environments, hydrophobic surfaces showed less bacterial adhesion when compared to the hydrophilic ones. , Herein, further investigation was undertaken by combining the water contact angles (WCAs) on the treated fabrics and bacterial antiadhesion rates (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…coli was obviously displayed in all of the antibacterial fabrics (F8, F9, F10, F11, and F3) as compared to that in the pristine fabric, with an especially great reduction for antibacterial fabrics (F9, F10, F11, and F3) due to the fluorine component. Sivakumar et al previously reported that hydrophilic surfaces prevent bacterial attachment and hydrophobic organisms have a greater propensity to attach to hydrophobic surfaces than hydrophilic ones in their work. However, a few researchers have found that in in vitro environments, hydrophobic surfaces showed less bacterial adhesion when compared to the hydrophilic ones. , Herein, further investigation was undertaken by combining the water contact angles (WCAs) on the treated fabrics and bacterial antiadhesion rates (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial antiadhesion of treated fabrics was estimated, as reported by Oh et al and Sivakumar et al with slight modifications. The treated fabrics and control (untreated fabrics) were vertically immersed in 25 mL of bacterial suspension (S.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cotton fabrics achieved bacterial antiadhesion mainly by hydrophobicity . Sivakumar et al developed a chalcone coating on cotton cloth to reduce bacterial adhesion . As an alternative, we recently developed a soft “surface stereochemistry” strategy, on the basis of a well‐accepted theory that cells could distinguish molecular chirality, to regulate microbial reversible adhesion in the initial stage of microbe–material interaction .…”
Section: Introductionmentioning
confidence: 99%
“…Serial tenfold dilutions of the suspension obtained were prepared and then 100 ll of dilutants were plated onto LB agar plates. After incubation for 48 h at 30°C, the number of colonies on the agar plates was measured and then colony forming unit (CFU) was calculated [30,31].…”
Section: Methodsmentioning
confidence: 99%